Relationship of Active Participation in Mosque Youth Activities with Youth Social Behavior in Kuranji Village, Guguak District, Lima Puluh Kota Regency - Agung Gunawan; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the low social behavior of Desa Kuranji, Gugua District, Lima Puluh Kota District. This study aims to see the relationship between active participation in mosque youth activities and the social behavior of adolescents in Kuranji Village, Guguak District, Lima Puluh Kota Regency. This type of research is a correlational descriptive study. The population in this study amounted to 22 people because in this study the entire population was sampled, so to determine the sample using the census method. The type of research data is about the relationship between the activeness of participating in mosque youth activities with the social behavior of adolescents in Kuranji Village, Guguak District, Lima Puluh Kota Regency. While the techniques used in the data collection used questionnaires, the tools used were questionnaires, and data analysis techniques used the product moment formula. The findings of this study explained that the relationship between the activity of participating in mosque youth activities and the social behavior of adolescents in Kuranji Village, Guguak District, Lima Puluh Kota Regency is low.Keywords: Activities, Social Behavior, Participation